Algunas reflexiones sobre liderazgo - Inostroza, Ivette (2004)
Nowadays, leadership is a topic that appears in many occasions and in different areas. Many times, it is considered that there is only one concept of leadership, and related concepts are mixed up such as power, authority, and obedience. This article presents a perspective to understand the topic and from here, to establish some special characteristics of the leadership in university life that allow people to mobilize in the search for goals that strengthen pertaining and institutional solidarity.